Electroplating zinc transition layer for electroless nickel plating on AM60 magnesium alloys - 王晓民 周婉秋 韩恩厚 (Transactions of Nonferrous Metals Society of China, 2006)
Electroplating zinc coating as transition layer of electroless nickel plating on AM60 magnesium alloys was investigated. The zinc film can be deposited in a pyrophosphate bath at 50-60 ℃ under current density of 0.5-1.5 A/dm^2. A new fore treatment technology was applied by acid cleaning with a solution containing molybdate and phosphorous acid, by alkaline cleaning in a bath containing molybdate and sodium hydroxide. The subsequent electroless plating was carried out in nickel sulfate bath. The SEM observation shows that the deposition is uniform and compact. The polarization curve measurements show that the corrosion potential of the zinc plating in 3.5% NaCl is about -1.3 V（vs SCE） which is noble than that of magnesium substrate. The zinc eleetroplating can be applied as the pretreatment process for electroless nickel plating on magnesium alloys.